Academic writing for international students of science - Bottomley, Jane (Routledge, 2015)
Includes bibliographical references and index; Academic Writing for International Students of Science will help international students to develop their command of academic scientific writing in English. It guides students through the writing process itself, and will help them to produce clear, well-written and well-organised essays and reports. The book covers a range of issues such as how to explain complex ideas clearly and concisely, how to develop a coherent argument, and how to avoid plagiarism by making effective reference to sources -- Provided by publisher